2017
DOI: 10.1016/j.jid.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Induces Increased Serine Protease Activity in Keratinocytes

Abstract: Bacteria that reside on the skin can influence the behavior of the cutaneous immune system, but the mechanisms responsible for these effects are incompletely understood. Colonization of the skin by Staphylococcus aureus (S. aureus) is increased in atopic dermatitis (AD) and can result in increased severity of the disease. In this study we show that S. aureus stimulates human keratinocytes to increase their endogenous protease activity, including specific increases in trypsin activity. This increased protease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 37 publications
(43 reference statements)
3
114
0
2
Order By: Relevance
“…The discrepancy with the protease/hemolysin effects mentioned above might be the use of human primary keratinocytes compared with immortalized cells. In a recent paper, it was shown that S. aureus induces keratinocyte‐intrinsic serine protease activity (e.g., kallikreins and trypsin) . However, the authors concluded that TLR activation was not involved in the induction, but rather secreted virulence factors .…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy with the protease/hemolysin effects mentioned above might be the use of human primary keratinocytes compared with immortalized cells. In a recent paper, it was shown that S. aureus induces keratinocyte‐intrinsic serine protease activity (e.g., kallikreins and trypsin) . However, the authors concluded that TLR activation was not involved in the induction, but rather secreted virulence factors .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this penetration of S. aureus into the skin may be linked to the differences Liu et al (2017) observed in subcutaneous versus epicutaenous S. aureus infections. Furthermore, we have shown that a secreted S. aureus factor(s) can stimulate human keratinocytes to increase expression of epithelial serine proteases that further damage the skin barrier (Williams et al, 2017). These S. aureus -induced serine proteases have been shown to stimulate the protease-activated receptor 2 (PAR-2) in keratinocytes to induce IL-1-type cytokines.…”
mentioning
confidence: 99%
“…Although in vitro studies of the effect of S. aureus on skin cells is important mechanistically, in vivo murine models of live S. aureus colonization have provided even stronger evidence that S. aureus colonization can induce AD skin phenotypes. We have shown that colonization of murine skin by S. aureus directly induces serine protease activity that disrupts the epidermal barrier (Williams et al, 2017) and that expression of T helper type 2 cytokines in the skin (a hallmark of the AD phenotype) is dependent on proteases secreted by S. aureus (Nakatsuji et al, 2016). Additionally, Nakamura et al (2013) have observed that S. aureus delta toxin increases allergic responses and promotes both inflammation and desquamation of the skin surface.…”
Section: Recent Experimental Evidence That S Aureus Can Induce Ad-limentioning
confidence: 99%